2015
DOI: 10.1259/dmfr.20140204
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution in CBCT machines for dental/maxillofacial applications—what do we know today?

Abstract: Spatial resolution is one of the most important parameters objectively defining image quality, particularly in dental imaging, where fine details often have to be depicted. Here, we review the current status on assessment parameters for spatial resolution and on published data regarding spatial resolution in CBCT images. The current concepts of visual [line-pair (lp) measurements] and automated [modulation transfer function (MTF)] assessment of spatial resolution in CBCT images are summarized and reviewed. Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 50 publications
(81 reference statements)
4
127
0
10
Order By: Relevance
“…21 The measured limiting spatial resolution did not correlate with reconstructed voxel size, which is consistent with the measurements of Pauwels et al 22 and Bamba et al 15 The images are resampled for display purposes at the voxel spacing reported in the acquisition parameters. Although a general consistency was observed between limiting spatial resolution measured by the 10% MTF and visual inspection of the bar patterns, it is clear that the reported voxel size (reconstructed voxel size) provides only a crude prediction of the spatial accuracy.…”
Section: Discussionsupporting
confidence: 80%
“…21 The measured limiting spatial resolution did not correlate with reconstructed voxel size, which is consistent with the measurements of Pauwels et al 22 and Bamba et al 15 The images are resampled for display purposes at the voxel spacing reported in the acquisition parameters. Although a general consistency was observed between limiting spatial resolution measured by the 10% MTF and visual inspection of the bar patterns, it is clear that the reported voxel size (reconstructed voxel size) provides only a crude prediction of the spatial accuracy.…”
Section: Discussionsupporting
confidence: 80%
“…13 Patients cannot remain perfectly still during the full examination time owing to heart beat, breathing and unintentional movements. 8,9,17 It is obvious that clinicians should attempt to reduce the incidence of patent motion artefacts by using "best clinical practice techniques" to reduce/avoid patient movement during CBCT examination. 9 Therefore, attention should be paid to patient positioning, stabilization, instruction and monitoring methods.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that between 4.5% and 41.5% of CBCT examinations show artefacts suggestive of patient movement. 13,14,16 But, although some studies 7,8 report on the possible impact of motion artefacts on image quality, knowledge of which types and magnitudes of movements may considerably hamper the diagnostic outcome of a CBCT examination is still a key question. 8 Moreover, it is unclear whether observed artefacts in some studies 13,14,16 were in fact due to patient motion.…”
Section: Discussionmentioning
confidence: 99%
“…beam hardening and extinction artefacts related to metal), 7,8 the study considered only images of young patients with no metal inside the FOV, which relate to the majority of the child populations in Western countries. To provide a strong control group for image quality evaluation, the CBCT images of the moving patients were matched to those of non-moving patients according to age, diagnostic task, examined region, FOV and resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation